Identifikasi Peran Masyarakat dalam Pembangunan Kampung Kota Berkelanjutan - Yuliani, Sri; Nugroho, Purwanto Setyo; Iswati, Tri Yuni (ARSITEKTURA, 2021)
Sustainable City Development can be achieved with the active role of actors in development activities, one of which is the role of the community. This study aims to identify the role of the urban Kampung community in the sustainable development of Kampung Kota. The research location is in the city of Surakarta with a sample of Kampung Gendingan RW 15, Kelurahan Jebres, Kecamatan (district) Jebres. The study used qualitative methods, through observation, interviews and discussion groups with swot analysis. The results showed that the role of the community in the development of the urban village can be applied to the participation of concept formulation, design and management. The three roles of the urban village community will be able to form a unique and sustainable village model.